Tuning of the rotational transform in Wendelstein 7-X*Notice: This manuscript has been authored by Princeton University under Contract Number DE-AC02-09CH11466 with the U.S. Department of Energy. The publisher, by accepting the article for publication acknowledges, that the United States Government retains a non-exclusive, paid-up, irrevocable, world-wide license to publish or reproduce the published form of this manuscript, or allow others to do so, for United States Government purposes. (17th September 2019) - Lazerson, Samuel A.; Gao, Yu; Hammond, Kenneth; Killer, Carsten; Schlisio, Georg; Otte, Matthias; Biedermann, Christoph; Spolaore, Monica; Bozhenkov, Sergey; Geiger, Joachim; Grulke, Olaf; Nicolai, Dirk; et al.
Abstract: The control of rotational transform in Wendelstein 7-X (W7-X) is key to both the island divertor operation and safety of plasma facing components. The island divertor concept in W7-X relies on an edge flux surface with rotational transform of resonating with an intrinsic n / m = 5/5 resonance to form a five lobed island chain. This island chain intersects with divertor plates to give rise to the island divertor. Changes in the relative position of the rational surface and the divertor plates can result in changes in divertor performance, thus the control of the rotational transform is essential to operation of the W7-X device. During the first divertor campaign electromagnetic loads resulted in elastic deformations of the shaped modular stellarator coils. Such deformations made these coils more planar, reducing the vacuum rotational transform, subsequently shifting the resonance outward. Unintended plasma wall interactions provided the first clear evidence of this effect during plasma operation. Flux surface measurements were utilized to estimate the correct level of current in the planar coils for correction of, and found to be around ̃ . Scans of the planar coil current for iota correction were performed during plasma operation. These measurements suggest planar coil currents between −250 and ̃ would place the strike lines at the designed distance from the pumping gaps. Divertor Langmuir and upstream probe measurements confirm these estimates along with measurements of divertor neutral gas pressure.